The fundamental right to reinforced labor stability: scope of constitutional protection by way of protective action in Colombia - Delgado Motoa, Beatriz (DIXI, 2019)
Purpose: Labor stability is intended to give a permanent character to the employment relationship, in which the worker can voluntarily decide whether to continue in the job; and only in exceptional cases, the employer can resolve the relationship. In Colombia, there is relative stability; only in special cases there is absolute stability, in which the right to work is even stronger, so that in such events we can speak of a fundamental constitutional right to reinforced labor stability.Methodology: The article is based on the study of constitutional sentences, in order to show how the Constitutional Court has established the rules of the fundamental constitutional right to reinforced labor stability, and the scope of its protection through protective action sentences, starting with sentence C-470 of 1997, with a paper by Dr. Alejandro Martínez Caballero. The doctrine of the Constitutional Court is constructed through protective action sentences (type T sentences), constitutionality sentences (type C sentences) and unification sentences (type SU sentences).Findings and conclusions: The Constitutional Court has considered that there are some cases in which the right to labor stability, enshrined in Article 53 of the Political Constitution, deserves greater protection.
Keywords: Protective action; fundamental rights; labor stability; enhanced labor stability; social state under the rule of law